Brain-wide connections of the parvicellular subdivision of the basolateral and basomedial amygdaloid nuclei in the rats - Zhu, Ge; Chen, Sheng-Qiang; Ma, Run-Zhe; Cai, Hui-Ru; Zhang, Jin-Yuan; Peng, Yi-Min; Lian, Dian; Ding, Song-Lin (Frontiers in Neural Circuits, 2025)
As the core area of emotion regulation, the amygdala is involved in and regulates many related behaviors, such as fear, anxiety, depression, as well as reward, learning, and memory. Most previous connectional studies have focused on the anterior and middle parts of the basolateral nucleus (BL) and basomedial nucleus (BM) of the amygdala. Little is known about the brain-wide connections of the posterior part of the BL and BM (termed parvicellular subdivision of the BL and BM, i.e., BLpc and BMpc). In this study, brain-wide afferent and efferent projections of the BLpc and BMpc in the rats are investigated using both retrograde and anterograde tracing methods. Both common and differential connections of the BLpc and BMpc are revealed. Major common inputs of both regions originate from the ventral hippocampal CA1 and prosubiculum, sublenticular extended amygdala, anterior basomedial nucleus, midline thalamic nuclei, endopiriform nucleus, dorsal raphe, piriform cortex and lateral entorhinal cortex. The BLpc receives preferential inputs from agranular insular cortex, amygdalopiriform transition area, periaqueductal gray, parataenial nucleus and anterior cortical nucleus of the amygdala. The BMpc preferentially receives its inputs from the peripeduncular nucleus, paraventricular nucleus of thalamus, ventromedial hypothalamic nucleus (VMH), caudal bed nucleus of stria terminalis (BST), medial amygdaloid nucleus and posterior cortical nucleus of the amygdala. Major differential outputs of the BLpc and BMpc are also obvious. The BLpc projects mainly to nucleus accumbens, rostral BST, lateral central amygdaloid nucleus (Ce), intermediate BL and BM. The BMpc sends its main outputs to VMH, medial Ce, caudal BST, prosubiculum, and perirhinal-ectorhinal cortices. These major findings are further confirmed with anterograde viral tracing in mice. Compared with previous findings in monkeys, our findings in rodents suggest that the BLpc and BMpc have overall similar connectional patterns across species. In addition, some gene markers for BM subdivisions are identified. All these findings would provide an important anatomical basis for the understanding of emotion-related neuronal circuits and diseases and for cross-species comparison of the subcircuits in amygdaloid complex.